Multidimensional Cyclic Voltammetry Simulations of Pseudocapacitive Electrodes with a Conducting Nanorod Scaffold. Issue 13 (1st January 2017) - Mei, Bing-Ang; Li, Bin; Lin, Jie; Pilon, Laurent
Abstract : This paper aims to understand the effect of nanoarchitecture on the performance of pseudocapacitive electrodes consisting of conducting scaffold coated with pseudocapacitive material. To do so, two-dimensional numerical simulations of ordered conducting nanorods coated with a thin film of pseudocapacitive material were performed. The simulations reproduced three-electrode cyclic voltammetry measurements based on a continuum model derived from first principles. Two empirical approaches commonly used experimentally to characterize the contributions of surface-controlled and diffusion-controlled charge storage mechanisms to the total current density with respect to scan rate were theoretically validated for the first time. Moreover, the areal capacitive capacitance, attributed to EDL formation, remained constant and independent of electrode dimensions, at low scan rates. However, at high scan rates, it decreased with decreasing conducting nanorod radius and increasing pseudocapacitive layer thickness due to resistive losses. By contrast, the gravimetric faradaic capacitance, due to reversible faradaic reactions, decreased continuously with increasing scan rate and pseudocapacitive layer thickness but was independent of conducting nanorod radius. Note that the total gravimetric capacitance predicted numerically featured values comparable to experimental measurements. Finally, an optimum pseudocapacitive layer thickness that maximizes total areal capacitance was identified as a function of scan rate and confirmed by scaling analysis.